Gallium-68 Labeled Iron Oxide Nanoparticles Coated with 2,3-Dicarboxypropane-1,1-diphosphonic Acid as a Potential PET/MR Imaging Agent: A Proof-of-Concept Study - Karageorgou, MA; Vranjes-Djuric, S; Radovic, M.; Lyberopoulou, A.; Antic, B; Rouchota, M.; Gazouli, M.; Loudos, G.; Xanthopoulos, S.; Sideratou, Z.; Stamopoulos, D.; Bouziotis, P.; et al. (CONTRAST MEDIA & MOLECULAR IMAGING, 2017)
The aim of this study was to develop a dual-modality PET/MR imaging probe by radiolabeling iron oxide magnetic nanoparticles (IONPs), surface functionalized with water soluble stabilizer 2,3-dicarboxypropane-1,1-diphosphonic acid (DPD), with the positron emitter Gallium-68. Magnetite nanoparticles (Fe3O4 MNPs) were synthesized via coprecipitation method and were stabilized with DPD. The Fe3O4-DPD MNPs were characterized based on their structure, morphology, size, surface charge, and magnetic properties. In vitro cytotoxicity studies showed reduced toxicity in normal cells, compared to cancer cells. Fe3O4-DPD MNPs were successfully labeled with Gallium-68 at high radiochemical purity (> 91%) and their stability in human serum and in PBS was demonstrated, along with their further characterization on size and magnetic properties. The ex vivo biodistribution studies in normal Swiss mice showed high uptake in the liver followed by spleen. The acquired PET images were in accordance with the ex vivo biodistribution results. Our findings indicate that 68 Ga-Fe3O4-DPD MNPs could serve as an important diagnostic tool for biomedical imaging.